2016
DOI: 10.1002/2327-6924.12358
|View full text |Cite
|
Sign up to set email alerts
|

The perceived effects of electronic cigarettes on health by adult users

Abstract: Background and purpose There is a lack of research on perceived health effects of electronic cigarettes by adult users. Because more people are choosing electronic cigarettes (e‐cigarettes) in addition to, or instead of traditional cigarettes, it is important for the nurse practitioner (NP) to understand why. Methods A comprehensive literature search was conducted using four scholarly databases. The search strategy utilized remained consistent. Qualitative, quantitative, observational studies and meta‐analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…Reviews have been published on ENDS in general 1021 or on specific topics, including: health effects 2258 ; impact on smoking cessation 29,4043,45,47,48,51,5973 ; product features 22,39,4143,45,47,7477 ; potential to induce dependence 28,45,47,78,79 ; consumer perceptions 26,48,80,81 ; patterns of use 8,26,43,48,51,8290 ; and policies. 8,48,9198 Two conducted a bibliometric review of the ENDS literature 86,99 and 46% of the reviews were systematic.…”
Section: Contextmentioning
confidence: 99%
“…Reviews have been published on ENDS in general 1021 or on specific topics, including: health effects 2258 ; impact on smoking cessation 29,4043,45,47,48,51,5973 ; product features 22,39,4143,45,47,7477 ; potential to induce dependence 28,45,47,78,79 ; consumer perceptions 26,48,80,81 ; patterns of use 8,26,43,48,51,8290 ; and policies. 8,48,9198 Two conducted a bibliometric review of the ENDS literature 86,99 and 46% of the reviews were systematic.…”
Section: Contextmentioning
confidence: 99%
“…Despite the paucity of human data, there is a growing perception among lay adults that e-cigs are as risky as cigarettes (2123). Most professional organizations have been cautious in their assessment of what is known regarding benefits and risks of e-cigs (2427), reflecting the lack of data regarding e-cigs’ toxicity, particularly relative to that of cigarette smoke. Adding to the difficulty of providing evidence based policy recommendations is the considerable diversity of products in terms of devices, flavors, and solvents.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, e-cig acute health effects are minimal and short-lived (27, 205212). The most common adverse effects reported across studies were nausea, headache, cough, and mouth/throat irritation, which were similar or less compared to nicotine patches.…”
Section: Introductionmentioning
confidence: 99%
“…[1517] The evidence from the existing studies have indicated that during 2012–2013, the sale of e-cigarettes in convenience stores in the U.S. increased by 320%, 72%, and 82% for disposable e-cigarettes, starter kits, and cartridges, respectively. [18] Importantly, these studies found that e-cigarette use has been increasing among both adolescents[19] and young adults aged 18–25 years;[20] however, very limited policies and programs exist to address this emerging issue.…”
Section: Introductionmentioning
confidence: 99%